2020
DOI: 10.1002/slct.202002887
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasound‐Assisted Alkaline Extraction on Antioxidant Activity and Functional Characteristics of Chicken Feather Keratin Peptides

Abstract: In this research, we focus on enzymatic hydrolysis of chicken feathers, after chemical or chemical and ultrasound pretreatment. Our result illustrated that ultrasound pretreatment preserved the main structure and amino acid composition of extracted keratin as confirmed by the Fourier-transform infrared (FTIR) spectroscopy and gel-electrophoresis analysis. In addition, investigation showed that ultrasound-assisted chemical treatment was more effective on enzymatic hydrolysis and bioactivity as compared to only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…High levels of such sulphur-containing amino acids, particularly cysteine, have been suggested to account for the antioxidant activity of the feather keratin. The antioxidant properties have been attributed directly to disruption of the disul de bonds during keratinous material solubilisation, therefore freeing the highly reactive thiol functional groups (SH), that could act as scavengers to cellular oxidants [40]. It has been shown that the antioxidant action of protein hydrolysates involves such mechanisms as deactivation of reactive oxygen species, reduction of hydroperoxides, chelation of prooxidant metallic ions, and changes in the physical properties of food systems [41,42], pollutants and environmental toxins.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…High levels of such sulphur-containing amino acids, particularly cysteine, have been suggested to account for the antioxidant activity of the feather keratin. The antioxidant properties have been attributed directly to disruption of the disul de bonds during keratinous material solubilisation, therefore freeing the highly reactive thiol functional groups (SH), that could act as scavengers to cellular oxidants [40]. It has been shown that the antioxidant action of protein hydrolysates involves such mechanisms as deactivation of reactive oxygen species, reduction of hydroperoxides, chelation of prooxidant metallic ions, and changes in the physical properties of food systems [41,42], pollutants and environmental toxins.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Remarkably, bioactive peptides and proteins demonstrate properties akin to hormones or drugs, thereby playing a beneficial role in metabolic processes and contributing to human well‐being. Bioactive peptides are categorized based on their distinct biological activities, including but not limited to antihypertensive (Chen et al., 2023; Uluko et al., 2014), antioxidant (Alahyaribeik & Ullah, 2020; Alizadeh & Aliakbarlu, 2020; Ashraf et al., 2020), antibacterial (Aguilar‐Toala et al., 2020; Alizadeh & Aliakbarlu, 2020), immunomodulatory (Zhang, Huang, et al., 2019c), anticancer (Chan et al., 2011; Ma et al., 2022), hypocholesterolemic (Ashraf et al., 2020), and mineral‐binding peptides (Luo et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, chemical reduction, enzymatic extraction, and ultrasound-assisted alkaline extraction have been demonstrated in recent studies utilizing chicken feathers to produce keratin hydrolysates with antioxidant and antibacterial activities. [11][12][13][14] The antioxidant properties have been attributed to disruption of the disulfide bonds during keratinous material solubilization, therefore freeing the highly reactive thiol functional groups ( SH) that could act as scavengers to cellular oxidants. Furthermore, bioactivities of antioxidant peptides isolated from poultry keratins were also scrutinized.…”
Section: Introductionmentioning
confidence: 99%